Stablecoins: illusions, claims, and facts - Eichengreen, Barry (Henry Stewart Talks, 2022)
Stablecoin, Cryptocurrency, Digital wallet, Bank fees, Government regulation, Financial inclusion, Micro-lending, Pegged exchange rates, Consumer protection, Systematic stability, Basket-based stablecoin